Exploring Different Types of Artificial Intelligence Systems and Their Performance Outcomes - Dr. Akhilesh Saini,; Mrs. Deepika Sharma, (The Bioscan, 2025)
Artificial Intelligence (AI) systems are classified into distinct types based on their capabilities, ranging from simple reactive machines to hypothetical self-aware entities. This paper explores four AI types—Reactive Machines, Limited Memory, Theory of Mind, and Self-Aware AI—analysing their applications, strengths, limitations, and performance through experimental results. Experiments in image classification, autonomous navigation, and text generation demonstrate the superiority of Limited Memory AI over Reactive Machines. The study also discusses challenges, ethical considerations, and future directions for AI development. By synthesizing empirical data and literature, this paper provides a comprehensive resource for researchers and practitioners aiming to understand AI’s diverse landscape.